CGAS‐STING do it again: pivotal role in RNase H2 genetic disease. (24th March 2016) - Gentili, Matteo; Manel, Nicolas
Abstract : RNase H2 is a susceptibility gene for the Aicardi–Goutières syndrome (AGS), a genetic auto‐inflammatory disease. Mackenzie and colleagues now report a tractable mouse model for the disease, implicating the cGAS‐STING pathway. Abstract : A tractable new mouse model for Aicardi–Goutières syndrome (AGS) implicates the cGAS‐STING pathway for cytosolic nucleic acid sensing in this auto‐inflammatory disease.